The Effect of Tax Avoidance, Tax Rate Change, and Sustainability Disclosure on Earnings Management - Dinata, I Putu Hendy Bimantara; Asqolani, Asqolani (Economics and Finance in Indonesia, 2024)
This study aims to analyze the effect of tax avoidance, changes in tax rates, and sustainability disclosures on earnings management. The sample in this study is public companies listed on the IDX for the period 2018–2021. The results of this study indicate that tax avoidance has no effect on earnings management. In addition, after the reduction in the corporate income tax rate, companies tend to conduct earnings management to reduce revenue. In the sustainability aspect, environmental sustainability disclosure has no effect on earnings management, while social sustainability disclosure has a positive effect on earnings management. The results of this study can be a consideration for the DGT and OJK in evaluating policies to reduce corporate tax rates, and sustainability disclosures.